Amyloid pathology and axonal injury after brain trauma. (1st March 2016) - Scott, Gregory; Ramlackhansingh, Anil F.; Edison, Paul; Hellyer, Peter; Cole, James; Veronese, Mattia; Leech, Rob; Greenwood, Richard J.; Turkheimer, Federico E.; Gentleman, Steve M.; Heckemann, Rolf A.; Matthews, Paul M.; et al.
Abstract : Objective: To image β-amyloid (Aβ) plaque burden in long-term survivors of traumatic brain injury (TBI), test whether traumatic axonal injury and Aβ are correlated, and compare the spatial distribution of Aβ to Alzheimer disease (AD). Methods: Patients 11 months to 17 years after moderate–severe TBI underwent 11 C-Pittsburgh compound B ( 11 C-PiB)-PET, structural and diffusion MRI, and neuropsychological examination. Healthy aged controls and patients with AD underwent PET and structural MRI. Binding potential (BPND ) images of 11 C-PiB, which index Aβ plaque density, were computed using an automatic reference region extraction procedure. Voxelwise and regional differences in BPND were assessed. In TBI, a measure of white matter integrity, fractional anisotropy, was estimated and correlated with 11 C-PiB BPND. Results: Twenty-eight participants (9 with TBI, 9 controls, 10 with AD) were assessed. Increased 11 C-PiB BPND was found in TBI vs controls in the posterior cingulate cortex and cerebellum. Binding in the posterior cingulate cortex increased with decreasing fractional anisotropy of associated white matter tracts and increased with time since injury. Compared to AD, binding after TBI was lower in neocortical regions but increased in the cerebellum. Conclusions: Increased Aβ burden was observed in TBI. The distribution overlaps with, but is distinct from, that of AD. This suggests a mechanistic link between TBI and the development of neuropathologic features of dementia, which may relate to axonal damage produced by the injury.